Perbandingan Kombinasi Weight Shifting Exercise ditambah Electrical Muscle Stimulation dan Weight Shifting Exercise pada Kontrol Trunk Penderita Hemiparese Post Stroke - Rahardian, Ivan Aditya; Farida, Siti; Anna, Novita; Melda, Byba; Katmini, Katmini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Hemiparese post strokes often cause a balance disorder due to the changes in the muscle tone, which is where the change is causing the control disorder of the trunk. The trunk control disorder can affect the balance of static sitting, dynamic and coordination trunk. This research is a quantitative researcher with a quasi-experimental research design where the research design uses a pre-test post-test control group design. This research was conducted at the Ivan Group Physioterapy Clinic Palembang with a sample of 32 people who met the inclusion criteria, then were randomized into 2 groups, namely the treatment group that was given electrical muscle stimulation and weight shifting exercise and the control group that was given only weight shifting exercise. The result of the study based on the Wiloxcon test obtained a value of p= 0.000 for static, dynamic and coordination sitting balance in the treatment group and get the value of p= 0.000 for static sitting balance, dynamic, and coordination on the control group, which means there’s a sifnificant effect on both sample groups on the change in trunk control. The combination of electrical muscle stimulation and weight shifting exercise is more effective in improving trunk control in static and dynamic sitting balance than weight shifting exercise alone, but no more effective in improving trunk control in trunk coordination.Keywords: Electrical Muscle Stimulation; Weight Shifting Exercise; Control Trunk; Hemiparese